Noise Level Measurement in Educational Areas: Case Study SMAN 5 Bandar Lampung - Verza Dillano Gharata; Roy Candra P Sigalingging; Ihsanil Fakhri; Veronica Dwi Jacinda; Desi Mega Yulina (Universitas Bandar Lampung (UBL), 2026)
Acoustic comfort in educational environments is crucial for effective learning. This study aims to measure and evaluate noise levels at SMAN 5 Bandar Lampung, located adjacent to the Soekarno Hatta arterial road. The research employs a quantitative descriptive method with direct field measurements using a Sound Level Meter at five observation points at 5-meter intervals. Data were collected over four days during morning, afternoon, and evening periods. Results indicate that noise levels at all points (64–82 dBA) consistently exceed the national quality standard of 55 dBA. Primary noise sources include heavy vehicles, modified exhausts, and traffic congestion. The study concludes that the school environment is acoustically non-conducive, necessitating architectural mitigations such as vegetation barriers and improved facade insulation to reduce noise intrusion.